2021
DOI: 10.3389/fendo.2021.724911
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Bone Crosstalk in Chronic Obstructive Pulmonary Disease

Abstract: Sarcopenia and osteoporosis are common musculoskeletal comorbidities of chronic obstructive pulmonary disease (COPD) that seriously affect the quality of life and prognosis of the patient. In addition to spatially mechanical interactions, muscle and bone can also serve as endocrine organs by producing myokines and osteokines to regulate muscle and bone functions, respectively. As positive and negative regulators of skeletal muscles, the myokines irisin and myostatin not only promote/inhibit the differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 99 publications
(129 reference statements)
0
24
0
Order By: Relevance
“…A recent retrospective study also indicated that chair rising test maximum force and grip strength were positively correlated with cortical geometric and microarchitectural parameters at all measured sites ( 27 ). Moreover, accumulating evidence suggested that bone and muscle can secrete a variety of cytokines to modulate each other, including myostatin, irisin, interleukin 6, osteocalcin, RANKL, and osteoprotegerin ( 28 ). Notably, as muscle ages, pathophysiological processes in muscle function present as selective loss of fast motor neurons while progressive loss of skeletal muscle mass presents as atrophy of muscle fibers, loss of number of muscle fibers, and reduced number of satellite cells ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study also indicated that chair rising test maximum force and grip strength were positively correlated with cortical geometric and microarchitectural parameters at all measured sites ( 27 ). Moreover, accumulating evidence suggested that bone and muscle can secrete a variety of cytokines to modulate each other, including myostatin, irisin, interleukin 6, osteocalcin, RANKL, and osteoprotegerin ( 28 ). Notably, as muscle ages, pathophysiological processes in muscle function present as selective loss of fast motor neurons while progressive loss of skeletal muscle mass presents as atrophy of muscle fibers, loss of number of muscle fibers, and reduced number of satellite cells ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased IL-6 is also associated with muscle mass loss and bone loss. In addition, COPD patients exhibit an elevated MSTN in skeletal muscle, while the raised MSTN in the serum of COPD patients is negatively correlated with total muscle mass [ 128 , 129 ]. MSTN can inhibit myoblast proliferation and differentiation, and promote muscle atrophy, which functions as a potent negative regulator of skeletal muscle growth and development [ 129 , 130 ].…”
Section: Relationship Between Inflammation-related Diseases and Skele...mentioning
confidence: 99%
“…In addition, COPD patients exhibit an elevated MSTN in skeletal muscle, while the raised MSTN in the serum of COPD patients is negatively correlated with total muscle mass [ 128 , 129 ]. MSTN can inhibit myoblast proliferation and differentiation, and promote muscle atrophy, which functions as a potent negative regulator of skeletal muscle growth and development [ 129 , 130 ]. After MSTN binds to TGF-β receptor, it activates Smad2 and Smad3 and regulates the transcription of genes involved in the proliferation and differentiation of skeletal muscle precursor cells, as well as the transcription of MuRF1 and atrogin-1 in mature muscle fibers [ 131 ].…”
Section: Relationship Between Inflammation-related Diseases and Skele...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory mediators IL-2 and IFNγ were inversely correlated with bone metabolism in COPD ( Bon et al, 2010 ). Skeletal muscle dysfunction mediated by inflammation was also an important factor in COPD-induced osteoporosis ( Zhang and Sun, 2021 ). High expression of IL-6 in COPD patients disrupted muscle–bone crosstalk and inhibited the secretion of irisin from muscle, which was positive for bone formation.…”
Section: Introductionmentioning
confidence: 99%